GARLIC: IT'S ROLE IN ORAL AND SYSTEMIC HEALTH - K., Harini; Babu, Subash; Ajila, Vidya; Hegde, Shruthi (Journal of Health and Allied Sciences NU, 2013)
A range of treatment modalities are available for the treatment of different oral diseases.The frequent use and misuse of currently available therapeutic agents has led to the evolution of increased incidence of adverse effects and development of resistant strains. Hence the search for an alternative option continues. Medicinal plants have been used as traditional treatment agents since ages. Garlic (Allium sativum) has been recognized for a number of therapeutic properties in the traditional system of medicine. Allium sativum is traditionally employed to treat infection, colds, diabetes, heart disease, and a host of other disorders. Clinically, it has been evaluated for lowering blood pressure, cholesterol, and glucose concentration, as well as for the prevention of arteriosclerosis and cancer. It is well known for its potent anti- inflammatory, anti- oxidant, anti-bacterial and antimutagenic properties. This article aims to review the efficacy of garlic in maintaining oral health in particular and overall health in general.
Keywords: Garlic; Allium Sativum; P. gingivalis; Cardiovascular diseases